2009
DOI: 10.1074/jbc.m109.055798
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effects of the Plug, Helix, and N- and C-terminal Domains on Channel Properties of the PapC Usher

Abstract: The chaperone/usher system is one of the best characterized pathways for protein secretion and assembly of cell surface appendages in Gram-negative bacteria. In particular, this pathway is used for biogenesis of the P pilus, a key virulence factor used by uropathogenic Escherichia coli to adhere to the host urinary tract. The P pilus individual subunits bound to the periplasmic chaperone PapD are delivered to the outer membrane PapC usher, which serves as an assembly platform for subunit incorporation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 35 publications
3
67
0
Order By: Relevance
“…In the apo usher, in the absence of a polymerizing and/or anchored pilus, the β-sandwich PLUG occupies the inactive pore. The PLUG seems to be kept stable in the pore via its interactions with residues of the β-barrel interior wall as well as the β5-6-hairpin loop and an α-helix of the TD that caps the β5-6-hairpin loop (3,25). In the active form, as seen in the FimDCH structure, the FimD pore rearranges to a nearly circular pore of 32 Å diameter (5,24) and the PLUG is relocated to the periplasm, where it forms a high-affinity, stable interaction with the NTD (23).…”
Section: Significancementioning
confidence: 99%
“…In the apo usher, in the absence of a polymerizing and/or anchored pilus, the β-sandwich PLUG occupies the inactive pore. The PLUG seems to be kept stable in the pore via its interactions with residues of the β-barrel interior wall as well as the β5-6-hairpin loop and an α-helix of the TD that caps the β5-6-hairpin loop (3,25). In the active form, as seen in the FimDCH structure, the FimD pore rearranges to a nearly circular pore of 32 Å diameter (5,24) and the PLUG is relocated to the periplasm, where it forms a high-affinity, stable interaction with the NTD (23).…”
Section: Significancementioning
confidence: 99%
“…Mutations of the NTD or either CTD abolish pilus biogenesis (25,27). The Plug domain is also required for pilus biogenesis (29,30). A Plug-deleted PapC folds but does not assemble pili, suggesting that the Plug domain plays a direct role in catalyzing pilus biogenesis (29,30).…”
mentioning
confidence: 99%
“…The Plug domain is also required for pilus biogenesis (29,30). A Plug-deleted PapC folds but does not assemble pili, suggesting that the Plug domain plays a direct role in catalyzing pilus biogenesis (29,30). Binding studies have suggested that the chaperone-adhesin complex is initially targeted to the NTD of PapC (26), and this is thought to activate the usher protein such that the β-sandwich Plug domain shifts from the channel, where it is located in the apo usher, to the periplasmic space, resulting in an open translocation pore (28).…”
mentioning
confidence: 99%
“…One major step in usher activation is the swinging out of the plug from its position within the usher pore lumen to its position in the periplasm where it interacts with the usher NTD. Electrophysiological studies suggested that both the NTD and the CTDs are involved in gating the usher, even in the absence of a translocation substrate [61], with only the FimH adhesin being able to stabilize the plug-NTD interaction in the open state while reaching out for the pore [43,47] ( figure 4, view b). Recently, it was proposed that the lectin domain of FimH actively displaces the plug domain, because the plug domain was calculated to have weaker interactions with the usher lumen than the lectin domain of FimH [27].…”
Section: Subunit Ordering and Pilus Elongation: The Usher's Rolementioning
confidence: 99%
“…Recently, it was proposed that the lectin domain of FimH actively displaces the plug domain, because the plug domain was calculated to have weaker interactions with the usher lumen than the lectin domain of FimH [27]. Deletion of the plug domain showed that it is essential in pilus biogenesis [61,62], its role in active subunit recruitment becoming recently apparent: the NTD of PapC alone was only able to bind PapD-PapG and PapD-PapE, but not the other chaperone-subunit complexes PapD-PapK/A/H, whereas an NTD-plug complex is able to bind all chaperone-subunit complexes [47]. ( figure 4, view c).…”
Section: Subunit Ordering and Pilus Elongation: The Usher's Rolementioning
confidence: 99%